Gasification of Nickel-Preloaded Oil Palm Biomass with Air - Syed Shatir A. Syed-Hassan; Siti Nor Izuera Nor-Azemi (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
This study experimentally investigates the gasification of nickel-preloaded oil palm biomass as an alternative catalytic approach to produce clean syngas. To eliminate the use of catalyst support, nickel was added directly to the oil palm mesocarp fiber via ion-exchange using an aqueous solution of nickel nitrate. Nickel species was found to disperse very well on the biomass at a nano-scale dispersion. The presence of the finely dispersed nickels on biomass enhanced syngas production and reduced tar content in the producer gas during the air gasification of biomass. It is believed that nickel particles attached on the biomass and its char promote the catalytic cracking of tar on their surface and supply free radicals to the gas phase to enhance the radical-driven gas-phase reactions for the reforming of high molecular weight hydrocarbons. The unconsumed nickel-containing char shows great potential to be re-utilised as a catalyst to further enhance the destruction of tar components in the secondary tar reduction process.